A lot of icing but little cake? Taking integrated reporting forward. (10th November 2016) - Perego, Paolo; Kennedy, Steve; Whiteman, Gail
Abstract: Integrated reporting has fast emerged as a new accounting practice to help firms understand how they create value and be able to effectively communicate this to external stakeholders. While insightful experiences from the early-adopters of integrated reporting start to accumulate, the development of the field and how integrated reporting may be successfully implemented remains challenging and contested. Several issues are still controversial with no consensus reached on the central purpose about integrated reporting. This paper relies upon a qualitative approach to accomplish two objectives. First, we provide a review of the embryonic academic literature in the integrated reporting field in order to summarize extant knowledge. Second, in response to a gap in the literature on managerial perceptions concerning integrated reporting, we present the sensemaking approaches of three key experts impacting integrated reporting practices at the global level using semi-structured interviews. Our findings suggest that experts perceive the field to be fragmented and believe that most companies currently have weak understanding of the business value of integrated reporting. The experts give insights into how they perceive the field to be progressing despite challenges and on where they see improvements in the diffusion of practices in integrated reporting. Our study contributes to this special issue by reframing the existing implementation challenges of integrated reporting into promising and inclusive research opportunities that align the priorities of both academia and business. Highlights: Comprehensive review of embryonic academic literature on integrated reporting (IR). Insights from three top business experts and field level entrepreneurs of IR. Experts perceive IR as a diverse and incoherent field due to a weak corporate understanding of IR. Despite challenges, experts agree that the IR field shows progress. We propose a future research agenda that can help IR address business needs.